Loading of bacterial nanocellulose hydrogels with proteins using a high-speed technique - Mueller, Astrid; Wesarg, Falko; Hessler, Nadine; Mueller, Frank A.; Kralisch, Dana; Fischer, Dagmar (Carbohydrate Polymers, 2014)
For the loading of the natural biopolymer bacterial nanocellulose (BNC) with drugs, usually an adsorption method has been described. In the present study, a high-speed loading technique based on vortexing was established for the incorporation of proteins in BNC as drug delivery system. Compared to the conventional technique, vortexing accomplished in 10 min the same protein loading capacity as the adsorption method in 24 h with comparable protein distribution and protein stability. Vortex loaded BNC demonstrated a retarded protein release with a lower total amount of released protein after 168 h compared to the adsorption loaded BNC. This was correlated with a densification of the fiber network as shown by electron microscopy and a reduced water holding capacity. These observations offer the possibility to control the drug release by selection of the preparation technique. © 2014 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial nanocellulose; Controlled release; Hydrogel; Protein delivery